Latest Quaternary palaeoceanographic change in the eastern North Atlantic based upon a dinoflagellate cyst event ecostratigraphy. Issue 5 (May 2016) - Harland, Rex; Polovodova Asteman, Irina; Morley, Audrey; Morris, Angela; Harris, Anthony; Howe, John A
Abstract: The analyses of dinoflagellate cyst records, from the latest Quaternary sediments recovered from DSDP Core 610A taken on the Feni Ridge in the southern Rockall Trough, and part of core MD01-2461 on the continental margin of the Porcupine Seabight in the eastern North Atlantic Ocean, has provided evidence for significant oceanographic change encompassing the Last Glacial Maximum (LGM) and part of the Holocene. This together with other published records has led to a regional evaluation of oceanographic change in the eastern North Atlantic over the past 68 ka, based upon a distinctive dinoflagellate event ecostratigraphy. These changes reflect changes in the surface waters of the North Atlantic Current (NAC), and perhaps the deeper thermohaline Atlantic Meridional Overturning Circulation (AMOC), driving fundamental regime changes within the phytoplanktonic communities. Three distinctive dinoflagellate cyst associations based upon both factor and cluster analyses have been recognised. Associations characterised by Bitectatodinium tepikiense (between 61.1 ± 6.2 to 13.4 ± 1.1 ka BP), Nematosphaeropsis labyrinthus (between 10.5 ± 0.3 and 11.45 ± 0.8 ka. BP), and the cyst of Protoceratium reticulatum (between 8.5 ± 0.9 and 5.2 ± 1.3 ka. BP) indicate major change within the eastern North Atlantic oceanography. The transitions between these changes occur over a relatively short time span (c.1.5 ka), given our sampling resolution, and have the potential to be incorporated into an event stratigraphy through the latest Quaternary as recommended by the INTIMATE (INTegrating Ice core, MArine and TErrestrial records) group. The inclusion of a dinoflagellate cyst event stratigraphy would highlight changes within the phytoplankton of the North Atlantic Ocean as a fully glacial world changed to our present interglacial.